Surgical treatment of hip arthritis - edited by William J. Hozack; Javad Parvizi; Benjamin Bender
Surgical Treatment of Hip Arthritis: Reconstruction, Replacement, and Revision, by William J. Hozack, MD, is a state-of-the-art reference that addresses the challenging issues you face in this rapidly growing segment of orthopaedic practice. Inside, you’ll find top surgical management strategies for all types of hip arthroplasty presented by leaders from around the world, along with discussions of possible complications, risks and benefits to specific patient populations, and more. A DVD, included with the text, presents step-by-step narrated videos of the surgeries covered in the book, enabling you to see these procedures in action. Best of all, this resource also offers access to a companion website where you will find the full text of the book, completely searchable